Encephalocraniocutaneous lipomatosis with calvarial exostosis - Case report and review of literature - Shruti Thakur; Vijay Thakur; Ram Gopal Sood; Charu Smita Thakur; Shweta Khanna (Indian Journal of Radiology and Imaging, 2013)
Encephalocraniocutaneous lipomatosis (ECCL), also known as Haberland syndrome, is a rare syndrome with unknown etiology. The syndrome is characterized by a triad of unique cutaneous, ocular, and central nervous system (CNS) manifestations. The cutaneous hallmark, nevus psiloliparus (NP), along with overlying alopecia is a constant feature. Choristoma of the eyelid is the most common ocular manifestation, while intracranial lipoma is the predominant CNS finding. Genetic counseling is required to emphasize that the disorder, although congenital, is not inheritable. We present a 21-year-old female with cutaneous, ocular, and CNS features satisfying the diagnostic criteria for ECCL. To our knowledge, this is the first case of ECCL having a large temporal exostosis. The objective of this article is to better understand the phenotypic spectrum of this syndrome whose molecular basis is still unknown.